Optimalisasi CHATGPT dalam Pembelajaran Bahasa Indonesia Berbasis Ekologi di SMAN 4 Pamekasan - Abdian Amien, Andito; Kusumawati, Hesti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The research examined the application of ChatGPT in optimizing ecology-based Indonesian language learning at SMAN 4 Pamekasan. The main focus was on how this AI helped students overcome challenges in descriptive writing, such as constructing effective sentences and maintaining logical flow while considering ecological aspects. Using a qualitative approach, data was collected through interviews and observations of eight 11th-grade students. The analysis showed that ChatGPT significantly improved students’ descriptive writing skills through direct feedback, grammar corrections, and assistance in idea organization. This technology also proved to enhance student engagement and ecological awareness in learning.